Expanding Human Computer Interaction Methods to Understand User Needs in the Design Process of Personal Health Systems - Siek, Katie A. (Yearbook of Medical Informatics, 2018)
Objectives: To review innovative human computer interaction methods researchers utilize to identify stakeholders' needs that inform the design of personal health systems outside of clinical environments.Methods: A selective review of recent literature.Results: Summaries of exemplar needs analysis papers showing how researchers utilize novel methods to surface the lived experiences of users.Conclusions: The medical informatics community is encouraged to ensure that we are designing health technology for all individuals - including underrepresented and underserved populations — by investigating the complex needs of target users. This paper summarizes the novel ways researchers have explored target populations via social media and engaged populations as part of the design team. Medical informaticians should continue investigating the soundness of these methods by comparing the design outcomes with currently utilized user-centered methods and to report on unintended consequences
Keywords: User-computer interface; needs assessment; social media; participatory design; usability methods